Mechanical analysis of the effects of implant position and abutment height on implant-assisted removable partial dentures. Issue 3 (July 2020) - Ohyama, Tetsuo; Nakabayashi, Shinya; Yasuda, Hiroyasu; Kase, Takeshi; Namaki, Shunsuke
Abstract: Purpose: An increasing number of clinical reports describe the use of dental implants as abutments in implant-assisted removable partial dentures (IARPD). We used three-dimensional finite element analysis to evaluate IARPD as a unilateral mandibular distal extension denture. Specifically, the mechanical effects of implant position and abutment height on the abutment tooth, denture, and denture-supporting tissue were assessed. Methods: The models analyzed were defects of the left mandibular second premolar and first and second molars prosthetically treated with an IARPD using one implant for each tooth position. There were two abutment heights: one equal to that of the mucosa and another that was elevated 2 mm above the mucosa. Six models were constructed. Results: For mucosal-level abutments, movement of the abutment tooth was lower for implants positioned distal to the abutment tooth than for those positioned medial to the abutment tooth. For elevated abutments, movement of the abutment tooth was lower for implants positioned medial to the abutment tooth than for those positioned distal to the abutment tooth. Conclusions: The mechanical effects on abutment teeth at the same implant position differed in relation to implant abutment height.